(untitled) (Research, Society and Development, 2020)
The attempt to repair skin wounds dates back many years. We have observed bone fragments for making needles, hair, fibers, and animal tissues as sutures and even applying sensors to accelerate the healing process throughout history. Despite all the developments, the need for a qualified professional and prior local anesthesia to perform the suture still represent obstacles. The present study aimed to create 3D printing pieces containing N42 neodymium magnets to be fixed to the skin with adhesive tape to promote skin wounds’ closure without the need for anesthesia. A descriptive, experimental study was carried out, divided into the Patent search, Ideation and creation, 3D Modeling, 3D printing of structural parts, Assembly, and Testing on artificial skin. ABSplus® plastic parts were created through 3D printing that received N42 neodymium magnets and the application of a double-sided adhesive to attach to the skin. A perilesional arrangement was simulated with the pieces created using an artificial skin model (EasySuture® Standart) after making the incision. After applying the pieces containing N42 neodymium, there was a perfect coaptation of the lesion’s edges without detecting interspersed spaces in the longitudinal axis of the incision. The research resulted in creating a prototype that needs improvements and industrial adaptations for viable use in surgical practice.